Measuring occupational performance supporting best practice in occupational therapy - Law, Mary C.; Baum, Carolyn Manville; Dunn, Winnie (SLACK Incorporated, 2017)
This book summarizes the measurement tools needed to assess client occupational performance, to provide the best intervention, and to document the effectiveness of that intervention. These measurement tools are not just a compilation of all that are available for measurement relevant to occupational therapy; they are an elite group of tools carefully selected by the editors through a process of rigorous theoretical, clinical, and scientific reasoning.